Association between sleep duration and sleep quality with pre-sarcopenia in the 20-59-year-old population: evidence from the National Health and Nutrition Examination Surveys 2005-2014 - Xiuxun Dong; Lei He; Li Zhang; Yang Shen (BMC, 2024)
Abstract Background Sarcopenia is a musculoskeletal disease characterized by a significant reduction in muscle mass, strength, and performance. As it mostly affects older adults, it is often recognized as a disease of old age. However, sleep is also closely related to its development. Hence, it becomes critical to explore the relationship between sleep and sarcopenia in populations under 60 years of age to develop strategies for preventing sarcopenia. We here aim to explore the specific association between sleep duration and sleep quality with pre-sarcopenia in the non-elderly population using large population samples. Methods This study involved 7,187 participants aged 20-59 years from the National Health and Nutrition Examination Survey (NHANES) conducted between 2005 and 2014. Pre-sarcopenia is defined based on the appendicular skeletal muscle mass (ASM) adjusted for body mass index (BMI). Self-reported sleep duration was categorized into three groups: <6 h (short sleep), 6-8 h (normal sleep), and > 8 h (long sleep). Sleep quality was assessed based on the Sleep Disorder and Trouble Sleeping Questionnaire. Univariate analysis and multivariate logistic regression were used to examine the relationship between sleep duration and sleep quality with pre-sarcopenia. Results Sleep quality was significantly linked with the risk of pre-sarcopenia (OR 1.72, 95% CI 1.36-2.18, P < 0.01). Longer or shorter sleep duration did not affect the risk of pre-sarcopenia, in contrast to normal sleep duration. Subgroup analysis demonstrated a more pronounced association in individuals who are > 40 years old (P < 0.01), non-Hispanic (P ≤ 0.01), overweight (P < 0.01), have a higher income (P < 0.01), and are more educated (P ≤ 0.01). Moreover, this association was noted in populations with or without smoking (P < 0.01) and alcohol consumption (P < 0.01), hypertension (P < 0.01) and diabetes (P ≤ 0.02). Conclusion Sleep quality is associated with an increased risk of pre-sarcopenia, while sleep duration is not in the population aged 20-59 years. Further prospective cohort studies with a large sample size are needed to determine causality and develop effective interventions for preventing sarcopenia in the population aged 20-59 years.